Distribution of ciguateric dinoflagellates, Gambierdiseus toxicus and Ostreopsis spp. in algal substrates off Sibuyan Island, Romblon - Geguira, Ma. Connie P. (Iloilo City, 2006)
A short term distribution of ciguateric benthic dinoflagellates, Gambierdiscustoxicus and Ostreopsis spp. In the divisions of Chlorophyta, Phaephyta,andRhodophyta in San Fernando and Cajidiocan reefs, Sibuyan Island, Romblon was evaluated from February to April 2000. Extensive algal substrates collection with line-quadrat transect method was carried out toevalaute interspecific algal-host preference. Ostreopsis spp. Were widely and abundantly (2,234.8 cells/cm2 total mean density) distributed in Laurencia, the dominant red macroalgae in both reefs. Gambleerdiscustoxicus (624.7 cells/cm2 total mean density) was found associated with Ostreopsisin both sites, albeit at lower densities in Cajidiocan. Ciguatericdinoflagellates showed no algal host specificity but their occurrence and abundance in algal substrate may be related to the accessibility of macroalgae together with other factors such as time, location, water depth and movement and algal cover that seemed to be directly involved in the distribution of these dinoflagellates in the area.
Thesis (M.S. Fisheries-Aquaculture) -- U.P. in the Visayas, 2006.
Keywords: Ciguateric dinoflagellates; Algal substrates; Sibuyan Island, Romblon